Vascular and Interventional Radiology in Sudan - Alaaeldeen Mohammed Mohammed (The Arab Journal of Interventional Radiology, 2021)
There are only 4 interventional radiologists working in Sudan with many difficulties such as lack of resources and high cost of interventional equipments and procedures. This result in shortage of interventional radiology services which is severely affecting the quality of patient care.